Proactive Risk Management using Healthcare Failure Mode Effect Analysis Tool to Improve Medication Management Process - Rahman, Tahmina; Ahmed, Rezina (Pulse, 2024)
Proactive risk management program is essential to maintain the quality and safety of patient care, treatment, and services within a healthcare system. According to the Joint Commission, hospitals need to adopt a proactive approach for risk management and develop risk mitigation strategies to reduce or eliminate the potentially harmful impact of possible risk. There are multiple tools that can be used for proactive analysis. Leaders of Evercare hospital Dhaka selected Healthcare FMEA tool to identify the potential failure modes in the current medication management process as it is one of the complex and high processes in healthcare settings. A multidisciplinary Healthcare FMEA team was formed comprising physician, nurse, pharmacist, quality, IT personnel and senior managements of EHD to conduct Healthcare FMEA. After completing Healthcare FMEA, twenty failure modes(n-20) and fifty-nine potential causes(n-59) of failure modes were detected in existing medication management process of EHD. The hazardous score was Two hundred & seventeen (n-217). There were Twelve major failures modes with higher hazardous score. Healthcare FMEA team members decided to eliminate major failures and actions were taken to control these failures. The main objective of this study is to maintain the medication error of EHD within the target (2/1000 patient days) by implementing required strategies and redesigning existing medication management process. The limitation of this study was it is a time-consuming process, it only helps to identify the possibilities of fail; it does not eliminate them, additional efforts are required to develop corrective action. Pulse Vol.15, 2023 P: 28-33